Development Of Flipbook Media In Learning And Recognition Of Flat Building Shapes In Stimulating Children's Knowledge - Wahyuningtyas, Dessy Putri; Rofi’i, Agus; Aziz, Firman; Fajriana, Fajriana; Kurniawan, Andri (UNIVERSITAS PAKUAN, 2023)
This research aims to develop interactive flipbook media as a learning instrument and introduction to flat shapes for enhancing elementary school students' knowledge. Using the ADDIE model, learning media are created by analyzing the learning requirements and knowledge of children in relation to the material of flat shapes during the analysis phase. In addition, during the design phase, the structure, content, and interactivity are tailored to the requirements of children. The evaluation stage was conducted by three subject matter experts who assessed seven aspects, of which one was rated as excellent, five as acceptable, and one as requiring improvement; specifically, the aspect of student participation and interaction. This study indicates that interactive flipbook media can be useful for teaching and learning about flat shapes in elementary school. This media can increase children's comprehension, interest, and motivation to learn, and help them make connections between the concepts of flat shapes and their commonplace lives.